COOPERATION OF FRUIT AND VEGETABLE PRODUCTS AND WAYS TO IMPROVE ITS EFFICIENCY - Ergashev, Rakhmatulla (Innovatsion texnologiyalar, 2024)
The problem of increasing its economic efficiency based on the establishment of a fruit and vegetable cluster cooperation system in current agricultural practice is the economic efficiency of fruit and vegetable cooperation, taking into account their wide use in the activities of fruit and vegetable cooperatives agroclusters, farmers and farms, as well as integration systems. Proposals and recommendations have been developed in order to improve the production and to satisfy the population's demand for fruits and vegetables. One of the basic ways to solve this problem is to achieve economic efficiency by connecting agroclusters, farmers and farms to the cooperative system of fruit and vegetable products, as well as the wide use of the activities of the integration system in the distribution of fruit and vegetable products. According to the results of the research, the organization of economic relations related to the process of growing fruit and vegetable products, storage, processing and sale on the basis of cooperation is highly profitable and effective for agroclusters, farmers and farms.